Synergy of Laz Harfa Institution with Village Government in Economic Empowerment of the Community of Bojongmanik Village, Sindangresmi District, Pandeglang Regency - Ombi Romli; Emiliawati Emiliawati (Business and Investment Review, 2024)
The synergy between the Harapan Dhuafa Amil Zakat Institution (LAZ Harfa) and the Bojongmanik Village Government represents a strategic collaboration in empowering rural community economies. This study aims to analyze the process and implementation of community empowerment programs conducted through mentoring, training, and local economic potential development. The research uses a qualitative descriptive method, employing observation, interviews, and documentation as data collection techniques. The results indicate that the collaboration between LAZ Harfa and the village government has successfully strengthened community capacity in managing local resources, increased household income, and fostered economic independence among villagers. Moreover, this synergy plays a vital role in cultivating social awareness and collective responsibility toward sustainable rural development. This collaborative model is expected to serve as a best practice for other social institutions and village governments in achieving independent and prosperous communities.